Extubation Failure and Timing to Tracheostomy in Children Surviving Acute Neurological Injury - Ethan L. Gillett; Sneha Jayadeep; Chary Akmyradov; Salim Aljabari (Children)
Background/Objectives: Critically ill patients with acute neurological injury commonly require intubation. The true incidence of and risk for extubation failure in pediatric patients with an acute neurologic injury is not well reported, making the assessment of these patients for extubation readiness or the need for tracheostomy challenging. This study aims to better delineate the incidence of extubation failure and factors associated with the need for tracheostomy in pediatric patients surviving an acute neurologic injury. Methods: We conducted a retrospective cohort study using the Virtual Pediatric System (VPS) database of neonates, infants, children, and adolescents < 18 years of age with a neurological injury requiring intubation from 2012 to 2022. Demographic and clinical variables were compared between subjects that were successfully extubated, those with early tracheostomy placement (≤14 days), and those with late tracheostomy placement (>14 days). Results: Of the 38,810 enrolled subjects, 37,661 (97.04%) were successfully extubated, 481 (1.24%) underwent early tracheostomy, and 668 (1.72%) underwent late tracheostomy. The most common etiologies were seizures (60.6%), trauma (20.9%), and intoxication (9.1%). The successfully extubated subjects had a higher median initial GCS score (8 vs. 5 and 4, p < 0.001) and fewer extubation attempts (1 vs. 3 and 3, p < 0.001) than the tracheostomy cohorts. There was a significant difference in median ICU days between the three groups (2.52 vs. 18.3 vs. 38.3, p < 0.001). Conclusions: The majority of pediatric patients requiring intubation following an acute neurological injury can be successfully extubated. Among patients requiring a tracheostomy, those who received it early had significantly shorter ICU and hospital stays.